2014
DOI: 10.4269/ajtmh.13-0426
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasite Co-infection among Pulmonary Tuberculosis Cases without Human Immunodeficiency Virus Infection in a Rural County in China

Abstract: Abstract. Epidemiologic studies of co-infection with tuberculosis (TB) and intestinal parasites in humans have not been extensively investigated in China. A cross-section study was conducted in a rural county of Henan Province, China. Pulmonary TB (PTB) case-patients receiving treatment for infection with Mycobacterium tuberculosis and healthy controls matched for geographic area, age, and sex were surveyed by using questionnaires. Fecal and blood specimens were collected for detection of intestinal parasites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
5
26
7
Order By: Relevance
“…Patients with BMI < 18.5 were 3.511 (95% CI = 1.646–7.489) times at higher risk of acquiring helminth co-infection. Findings from China go in line with our results [11, 23]. This is expected as helminths cause under-nutrition [27, 28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Patients with BMI < 18.5 were 3.511 (95% CI = 1.646–7.489) times at higher risk of acquiring helminth co-infection. Findings from China go in line with our results [11, 23]. This is expected as helminths cause under-nutrition [27, 28].…”
Section: Discussionsupporting
confidence: 91%
“…In rural areas where majority of people walk bare foot, hook worms may be more prevalent than A. lumbricoides . Xin et al [23] and Alemayehu et al [13] reported walking bare foot is associated with helminth infection. May be because most respondents are urban residents, shoe wearing habit was not associated factor in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was suffering from tuberculosis. Intestinal parasitic coinfection with tuberculosis without HIV infection has been studied in the past [32]. Studies also have shown that coccidian parasites infect the immunocompromised patients suffering from HIV [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal parasitic infections in majority of the cases are asymptomatic; however, IPIs can cause a whole range of clinical symptoms such as watery or mucoid diarrhea, dehydration, vomiting and nausea, abdominal pains and fever, vitamin deficiencies, growth retardation in children, iron deficiency anemia as well as mental and physical health disorders (3,5). In addition, the chronic IPIs are related with the risk of other infections, such as malaria, tuberculosis and viral infections (6,7), especially in immunocompromised individuals (8).…”
Section: Introductionmentioning
confidence: 99%